2021
DOI: 10.1021/acssuschemeng.1c05395
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Natural Products by Direct Formation of Eutectic Systems

Abstract: A eutectic system forms when two or more substances reorganize into a superlattice that has a lower melting point than each of the individual components. Deep eutectic solvents (DESs) are environmentally friendly solvents often used for the dissolution, extraction, and separation of chemical compounds. Instead of using DESs for extraction, hydrogen bond acceptors (HBAs) or hydrogen bond donors (HBDs) can be used to form a deep eutectic system (DESys) directly with the target compound for one-step dissolution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In addition, a recent study demonstrated the direct use of ChCl DESs using malonic acid, lactic acid, glycerol, ethylene glycol, urea, and methyl urea for the extraction of curcuminoids . The results demonstrated that ChCl/ethylene glycol (1:4) provided the best extraction yield of curcuminoids of 2.543 mg/g . In comparison to our current work, DES-B5 exhibits the greater extraction yield (55.86 mg/g), compared to the method using ChCl/ethylene glycol DES solvent recently published.…”
Section: Results and Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In addition, a recent study demonstrated the direct use of ChCl DESs using malonic acid, lactic acid, glycerol, ethylene glycol, urea, and methyl urea for the extraction of curcuminoids . The results demonstrated that ChCl/ethylene glycol (1:4) provided the best extraction yield of curcuminoids of 2.543 mg/g . In comparison to our current work, DES-B5 exhibits the greater extraction yield (55.86 mg/g), compared to the method using ChCl/ethylene glycol DES solvent recently published.…”
Section: Results and Discussionsupporting
confidence: 44%
“…Although the CHEM21 toolkit demonstrated that ethanol had the lowest PMI for curcuminoid extraction under ultrasonication, the overall results suggested that DES-B5 had the greenest performance for curcuminoid extraction on account of its excellent properties, including high yields, biodegradability, low toxicity, being inexpensive, and readily available. In addition, a recent study demonstrated the direct use of ChCl DESs using malonic acid, lactic acid, glycerol, ethylene glycol, urea, and methyl urea for the extraction of curcuminoids . The results demonstrated that ChCl/ethylene glycol (1:4) provided the best extraction yield of curcuminoids of 2.543 mg/g .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The melting points of DESs are much lower than those of the individual components . Multiple excellent advantages of DESs, such as easy synthesis, low cost, less toxicity, environment friendliness, and good biocompatibility, make them attractive in various fields, including synthesis, catalysis, extraction, drug delivery, and so forth. In the recent five years, DESs have shown the potential as alternative solvents to regulate the crystallization process and tailor the crystal structure. , Belviso et al published the first study of protein crystallization in DESs and found that the crystallization rate could be regulated by tuning DES hydration . Hall’s group found that polymorphs of paracetamol and metaxalone could be obtained from volatile DESs by adjusting the molar ratios of DES components .…”
Section: Introductionmentioning
confidence: 99%
“…It also has the characteristics of low cost, easy preparation, and high recyclability [ 11 ]. In recent years, DESs have shown potential application value in bio-catalysis [ 12 ], natural product extraction [ 13 ], electrodeposition [ 14 ], material synthesis [ 15 ], and extraction of bioactive components [ 16 ]. Like ionic liquids, DESs also have a good delignification effect.…”
Section: Introductionmentioning
confidence: 99%